Analysis of binary Aluminium-Magnesium products with varying compositions and optimum flowbility, tensile strength and hardness - Mohd Ichwan Nasution, Ir.; Murizam, Darus; Noor Mariamadzliza, Mohd Nan; Noor Azira, Mohd Noor; Kamrosni, Abdul Razak (Universiti Malaysia Perlis, 2009)
This reasearch is to investigate how far the influence on mechanical properties and microstructure of varying aluminium-magnesium alloy using CO2 moulding process. Casting is a process that can produce a complex and complicated component. In this reasearch, three composition samples will be prepared into casting method and determine its properties. Main parameter used in this process is varying composition between aluminium and magnesium. Propose of this reasearch is to see the changes of the mechanical characteristic and microstructure base on different composition according to aluminium-magnesium alloys. Mechanical charactristic quality that will be consider, which are of major concern, included tensile strength, hardness and flowability, while microstructure reasearch is to see the microstructure changes. Tensile strength, and hardness test will help to obtain grain sizes of aluminium-magnesium alloys. The flowability at its given composition level will be determinate to be used in various production criteria.